Recurrent DVT and Mediastinal Adenopathy: A Silent Manifestation of Gallbladder Cancer - Zakaria Alagha MD, Msc; Tata Avalishvili MD; Samuel Crow; Samhitha Gundakaram MD; Thomas McIntosh MD; Muhammad Ghallab MD, FACP; Yousef Shweihat MD, FCCP; Bisher Mustafa MD, FACP; Amro Al-Astal MD, FCCP; Ahmed Mahdi MD, FACP (Journal of Investigative Medicine High Impact Case Reports)
Recurrent deep vein thrombosis (DVT) is a common complication, particularly in cancer patients. We present a case of a 50-year-old male with a history of a previous DVT. Despite therapeutic anticoagulation with apixaban, the patient developed recurrent DVT involving the common femoral, popliteal, and foreleg veins. He was started on a heparin drip in the hospital, but despite this, his DVT worsened. Imaging studies revealed mediastinal and hilar lymphadenopathy, raising suspicion of malignancy. The workup revealed elevated tumor markers, while the thrombophilia panel was unremarkable. Despite aggressive management, including mechanical thrombectomy, catheter-directed thrombolysis, and the placement of an inferior vena cava filter, the patient’s condition continued to deteriorate. A biopsy of the mediastinal lymph nodes revealed poorly differentiated mucinous adenocarcinoma with molecular analysis consistent with hepatobiliary origin, and the patient was diagnosed with stage IVB gallbladder cancer. Given the rarity of gallbladder cancer and its association with hypercoagulability, this case highlights the importance of considering cancer as an underlying cause of recurrent DVT after ruling out common causes. Early recognition and a comprehensive diagnostic approach are essential for managing such cases. The patient was started on chemotherapy while maintaining anticoagulation for recurrent DVT.